Peran Program Corporate Sosial Responsibility (CSR) dalam Meningkatkan Kemandirian Ekonomi Perempuan : Studi Kasus Kelompok Wanita Berlian Progo Binaan PT Pertamina Patra Niaga Fuel Terminal Rewulu - Zukhruf Arifin; Rifaldi Maulyansyah; Pandu Prasojo; Putri Nur Alifah (Yayasan Literasi Sains Indonesia, 2024)
The ideal empowerment is one that involves the community in its processes towards changes that meet the needs of the people. However, currently the latest trend in society is the concept of empowerment that involves women in every process. Empowerment of women with the aim that they can be empowered and change for the sole purpose of being able to improve their degree of welfare both in terms of fulfilling their roles and well-being. This research departs from the background of the involvement of women's roles through company-assisted groups and looks at how the development and difficulties encountered to date with the aim of proving that the CSR program has brought a meaningful change to the role of women in the company's development area. This research will focus on Poncosari Village, Srandakan Subdistrict, Bantul Yogyakarta, which is a development area of one of the state-owned companies and see from the perspective of their fostered group which is one of the development groups of the company's CSR Program. This research will focus on understanding how the role of women in change through empowerment programs carried out by the company's CSR. The method used is a literature study and in-depth interviews to explain that the literature study relates to theoretical studies through related references. The results of the study found that the role of women through CSR-assisted groups has had positive implications for women in Poncosari Sub-district, Srandakan District, Bantul Regency. Women become empowered and able to compete with men in the fulfillment of their primary needs. How women can be empowered is due to the involvement of companies that focus on providing meaningful and sustainable CSR programs. The conclusion of this study is that the company's CSR program has provided meaningful changes to women who are members of the fostered group. Changes occur, departing from the condition of women who initially did not have a portion in the village, turned into development thanks to the Company's CSR program.